Lower adenoma miss rate with FUSE vs. conventional colonoscopy with proximal retroflexion: a randomized back-to-back trial - Papanikolaou, Ioannis S.; Apostolopoulos, Periklis; Tziatzios, Georgios; Vlachou, Erasmia; Sioulas, Athanasios D.; Polymeros, Dimitrios; Karameris, Andreas; Panayiotides, Ioannis; Alexandrakis, Georgios; Dimitriadis, George D.; Triantafyllou, Konstantinos (Endoscopy, 2017)
Background and study aims Full-spectrum colonoscopy (FSC) promises to increase adenoma detection by providing a wider field of view. The aim of this study was to compare adenoma miss rates of FSC with those of conventional colonoscopy complemented by right-colon re-examination using scope retroflexion (CC/R).Patients and methods At two tertiary endoscopy facilities, patients who were scheduled for colonoscopy for the assessment of symptoms or for colorectal cancer screening/surveillance were randomized (1:1) to undergo same-day, back-to-back colonoscopies (FSC or CC/R first), performed by one of five endoscopists who had documented adenoma detection rates > 35 %. Per-protocol data were analyzed. Results We randomized 220 patients. There were five FSC technical failures (three air pump and two left screen); therefore, 107 and 108 cases were analyzed in the FSC and CC/R index procedure arms, respectively. Withdrawal times were similar for FSC and CC/R (7.7 minutes vs. 7.6 minutes). Overall, we detected 3 cancers and 153 adenomas (FSC = 92; CC/R = 61); 81 were detected in the proximal colon, 3 of which were detected by retroflexed examination. By per-lesion analysis, FSC showed a significantly lower adenoma miss rate compared with CC/R overall (10.9 % [95 % confidence interval (CI) 3.8 to 18.1] vs. 33.7 % [95 %CI 23.4 to 44.1]) and in the proximal colon (13.9 % [95 %CI 2.6 to 25.2] vs. 42.2 % [95 %CI 27.8 to 56.7]). The advanced adenoma miss rate was lower with FSC overall (4.3 % [95 %CI – 4.0 to 12.7] vs. 25.9 % [95 %CI 9.4 to 42.5]). There were no adverse events. Conclusions FSC outperformed conventional colonoscopy with right-colon scope retroflexion in the detection of missed adenomas, both overall and in the proximal colon, even when performed by experienced endoscopists.Trial registered at ClinicalTrials.gov (NCT02117674).